Riskfactors of scabies in students of Aulia Cendikia Islamic BoardingSchool, Palembang - Fifa Argentina; Debby Handayati Harahap; Evi Lusiana (JURNAL KEDOKTERAN DAN KESEHATAN, 2019)
Abstract.Scabies is a skin disease caused by infestation and sensitization of Sarcoptesscabiei var. hominis. Scabies can infect everyone at all ages, races, genders and social economic levels. This disease is usually found in places such as dormitories, orphanages, prisons, islamic boarding schools that lack personal hygiene. Observational analytic research with cross sectional design has been carried out at boarding school Aulia Cendikia in Palembang from June to December 2017. There were 199 samples of students of Aulia Cendikia boarding school in Palembang city that met the inclusion criteria. In this study, there were no age differences between students with or without scabies (p = 0.374; p> 0.05). This study showed that the number of people per room was the factor that most contributed to the incidence of scabies (PR = 2.746, p = 0.002) followed by personal hygiene (PR = 2.333, p = 0.007) and gender (PR = 2.068, p = 0.019). Number of people in the room, personal hygiene and gender are risk factors for scabies at the Aulia Cendikiaislamic boarding school in Palembang.